2009
DOI: 10.1080/10409230903061207
|View full text |Cite
|
Sign up to set email alerts
|

An intracellular trafficking pathway in the seminiferous epithelium regulating spermatogenesis: a biochemical and molecular perspective

Abstract: During spermatogenesis, fully developed spermatids (i.e., spermatozoa) at the luminal edge of the seminiferous epithelium undergo 'spermiation' at stage VIII of the seminiferous epithelial cycle. This is manifested by the disruption of the apical ectoplasmic specialization (apical ES) so that spermatozoa can enter the tubule lumen and to complete their maturation in the epididymis. At the same time, the blood-testis barrier (BTB) located near the basement membrane undergoes extensive restructuring to allow tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
84
0
4

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
4

Relationship

5
3

Authors

Journals

citations
Cited by 113 publications
(89 citation statements)
references
References 167 publications
1
84
0
4
Order By: Relevance
“…These supports are mediated via gap junctions and perhaps intercellular bridges at the Sertoli-germ cell interface, including spermatogonia, spermatocytes, and step 1-7 spermatids (20,32). Once step 8 spermatids appear at stage VIII of the epithelial cycle, a testis-specific AJ known as apical ES arises, which replaces desmosome and gap junction to become the only anchoring device, and it persists through step 19 spermatids, until it is degenerated to allow the release of sperm at spermiation (5,6,22). The apical ES is typified by the presence of an array of actin filament bundles that lie perpendicular to the Sertoli cell plasma membrane apposing the step 8 -19 spermatid plasma membrane and are sandwiched in between the cisternae of endoplasmic reticulum and the Sertoli cell plasma membrane, surrounding almost the entire head of spermatids that confers both adhesion and polarity to spermatids (6,32,35).…”
Section: Discussionmentioning
confidence: 99%
“…These supports are mediated via gap junctions and perhaps intercellular bridges at the Sertoli-germ cell interface, including spermatogonia, spermatocytes, and step 1-7 spermatids (20,32). Once step 8 spermatids appear at stage VIII of the epithelial cycle, a testis-specific AJ known as apical ES arises, which replaces desmosome and gap junction to become the only anchoring device, and it persists through step 19 spermatids, until it is degenerated to allow the release of sperm at spermiation (5,6,22). The apical ES is typified by the presence of an array of actin filament bundles that lie perpendicular to the Sertoli cell plasma membrane apposing the step 8 -19 spermatid plasma membrane and are sandwiched in between the cisternae of endoplasmic reticulum and the Sertoli cell plasma membrane, surrounding almost the entire head of spermatids that confers both adhesion and polarity to spermatids (6,32,35).…”
Section: Discussionmentioning
confidence: 99%
“…At stage VIII of the seminiferous epithelial cycle, the BTB undergoes extensive restructuring to allow the transit of preleptotene spermatocytes from the basal to the apical compartment. At the same time, preleptotene spermatocytes differentiate into leptotene and zygotene spermatocytes (3) so that meiosis and postmeiotic germ cell development can take place in the apical compartment behind the BTB (2). While the BTB undergoes this cyclic restructuring throughout spermatogenesis, the immunological barrier conferred by the BTB is maintained at all time to segregate the postmeiotic germ cell development from the host immune system to avoid the production of antibodies against germ cell-specific antigens that attack its own sperms.…”
mentioning
confidence: 99%
“…While the BTB undergoes this cyclic restructuring throughout spermatogenesis, the immunological barrier conferred by the BTB is maintained at all time to segregate the postmeiotic germ cell development from the host immune system to avoid the production of antibodies against germ cell-specific antigens that attack its own sperms. Previous studies have shown that cytokines (e.g., TGF-β2 and TGF-β3) and testosterone are working in concert to facilitate the transit of spermatocytes at the BTB while maintaining the immunological barrier (2,4). For instance, testosterone maintains the immunological barrier by inducing de novo synthesis of junction proteins (e.g., claudins and occludin) (5-7) as well as transcytosis of proteins from other sites of the Sertoli cells to promote the assembly of "new" TJ fibrils behind a spermatocyte in transit (4).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the concave side of the spermatid heads in stage VII tubules was recently shown to be the site where extensive endocytic vesicle-mediated protein trafficking occurs, [58][59][60] so that 'old' apical ES proteins (e.g., b1-integrin, nectin-3, laminin-a3, -b3 and -c3 chains) can be endocytosed and recycled to the newly arisen apical ES in step 8 spermatids during spermiogenesis at stage VIII of the epithelial cycle. 46,61 Nonetheless, the finding that Bcrp is expressed stage specifically by late spermatids in the adluminal compartment 33 has shown that this efflux drug pump may be used by late-stage spermatids to safeguard their development by pumping out unwanted substances in the adluminal compartment prior to their transformation to mature spermatozoa. This possibility must be carefully evaluated in future studies.…”
Section: Bcrp and Spermatogenesis Xj Qian Et Al 457mentioning
confidence: 99%